GE_GERICHTE P/8142/2007 vom 15. Oktober 2007 - GE Cour de justice (2007)
; COCAÏNE ; CAS GRAVE ; INTERMÉDIAIRE ; FIXATION DE LA PEINE ; SURSIS À L'EXÉCUTION DE LA PEINE | LStup.19.1; LStup.19.2a; LStup.19.1.7; CP.47; CP.42